2002
DOI: 10.1002/1521-3765(20020104)8:1<171::aid-chem171>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

{FeCp}+-Induced Hexafunctionalization of Hexamethylbenzene with Dendrons for the Direct Synthesis of Redox-Active Iron-Centered Metallodendrimers

Abstract: Phenol tri- and nonaallyl dendrons (3 and 7, respectively) were functionalized at the focal position to give the new triallyl dendrons 4 and 6 and the nonaallyl dendrons 11 and 13 that contain a iodoalkyl or a bromobenzyl termini. All these dendrons were used for the [FeCp]+-induced hexafunctionalization of hexamethylbenzene in [FeCp(eta6-C6Me6)][PF6] (1) under mild conditions in the presence of KOH. These reactions directly yielded the 18-allyl and 54-allyl dendrimers 9, 10, and 14 with a [FeCp(eta6-arene)]+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Benzylic C−H bond activation in cationic arene-cyclopentadienyliron complexes and subsequent bond formation of the resulting neutral cyclohexadienyl species with various elements is a well-established general and useful procedure for effecting modifications on the structure of the arene ligand. 2b,, It is made possible by the enhancement of the acidity of the benzylic protons in the cationic complex. For instance, the p K a in DMSO has indeed been found to be about 14 units lower for the 18-electron complexes [CpM(η 6 -C 6 Me 6 )] + PF 6 - (M = Fe, Ru; p K a = 29) than for the free arene (p K a = 43). On the other hand, several authors 15a,21-23 have also demonstrated that deprotonation could occur at the amino substituent on the arene ligand and that subsequent treatment with an excess of alkylating reagents give rise to formation of new N−C bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Benzylic C−H bond activation in cationic arene-cyclopentadienyliron complexes and subsequent bond formation of the resulting neutral cyclohexadienyl species with various elements is a well-established general and useful procedure for effecting modifications on the structure of the arene ligand. 2b,, It is made possible by the enhancement of the acidity of the benzylic protons in the cationic complex. For instance, the p K a in DMSO has indeed been found to be about 14 units lower for the 18-electron complexes [CpM(η 6 -C 6 Me 6 )] + PF 6 - (M = Fe, Ru; p K a = 29) than for the free arene (p K a = 43). On the other hand, several authors 15a,21-23 have also demonstrated that deprotonation could occur at the amino substituent on the arene ligand and that subsequent treatment with an excess of alkylating reagents give rise to formation of new N−C bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Metal‐containing stars and dendrimers have been the focus of many research groups 19–32. Several different metals have been incorporated into macromolecules, including iron,33–36 ruthenium,37–42 and platinum 43, 44.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, (arene)Cr(CO) 3 complexes have emerged as versatile synthetic intermediates that are amenable to stereocontrolled side-chain functionalization and nucleophilic aromatic addition/substitution (S N Ar) processes . In addition to chromium, isoelectronic arene−metal complexes of (CO) 3 Mn(I) and cyclopentadienyl (Cp) Fe(II) also have been frequently employed in the context of complex molecule construction. , In contrast, the chemistry of related (η 6 -arene)CpRu(II) derivatives has not been extensively developed . Importantly, however, the CpRu(II) fragment offers several distinct advantages as an arene activating organometallic moiety in that arene ruthenium complexes can be prepared in high yield using exceedingly mild reaction conditions and coordination of the CpRu group is compatible with a wide range of preexisting arene ligand functionality.…”
Section: Introductionmentioning
confidence: 99%